2006
DOI: 10.1007/s10637-006-9012-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of amrubicin in previously untreated patients with extensive-disease small cell lung cancer: West Japan Thoracic Oncology Group (WJTOG) study

Abstract: Amrubicin was active for extensive-disease SCLC with acceptable toxicity. Further studies in combination with other agents for SCLC are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 17 publications
3
78
3
Order By: Relevance
“…In a phase I/II study of patients with non-small-cell lung cancer, the recommended dose was determined to be 45 mg/ m 2 /day for 3 consecutive days every 3 weeks (5). In a phase II study of SCLC, 35 patients with extensive disease (ED) were treated at the recommended dose, and a response rate of 75.8% and median survival time (MST) of 11.7 months were reported (6).…”
Section: Introductionmentioning
confidence: 99%
“…In a phase I/II study of patients with non-small-cell lung cancer, the recommended dose was determined to be 45 mg/ m 2 /day for 3 consecutive days every 3 weeks (5). In a phase II study of SCLC, 35 patients with extensive disease (ED) were treated at the recommended dose, and a response rate of 75.8% and median survival time (MST) of 11.7 months were reported (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, our observation suggests the possibility that AMR is optimal as a chemotherapeutic agent combined with STI571 in the treatment of SCLC. AMR, a totally synthetic 9-aminoanthracycline, demonstrated excellent anti-tumor activity as a single-agent or combination therapy for ED-SCLC (6,21). Therefore, given that SCF/c-kit-mediated autocrine signal activates Akt in SCLC in vivo, the combination of STI571 and AMR may be promising in the treatment of SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Although 57.6% of patients experienced nausea and vomiting during the phase II clinical trial (WJTOG study) that was conducted in Japan, grade 3 or higher nausea and vomiting were not observed during this trial [7]. However, since the WJTOG study sample size was small, the prophylactic antiemetic therapy during the observational period could not be clarified.…”
Section: Ivyspring International Publishermentioning
confidence: 93%